2019
DOI: 10.1016/j.jhealeco.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

[Job] Locked and [Un]loaded: The effect of the Affordable Care Act dependency mandate on reenlistment in the U.S. Army

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…Reexamining this question with longitudinal data could shed light on the degree to which individuals altered their incomes and bunched about these kinks, though the size of currently available public datasets may result in underpowered statistics. In addition, future work on the ACA should attempt to disentangle labor demand due to the employer mandate from labor supply among the general population (Kofoed & Frasier, 2019). Overall, this study is consistent with the previous retirement literature in finding that the provision of lower cost health insurance increases the likelihood of early retirement.…”
Section: Discussionsupporting
confidence: 87%
“…Reexamining this question with longitudinal data could shed light on the degree to which individuals altered their incomes and bunched about these kinks, though the size of currently available public datasets may result in underpowered statistics. In addition, future work on the ACA should attempt to disentangle labor demand due to the employer mandate from labor supply among the general population (Kofoed & Frasier, 2019). Overall, this study is consistent with the previous retirement literature in finding that the provision of lower cost health insurance increases the likelihood of early retirement.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the ACA Medicaid expansions for low-income parents reduced the likelihood that parents avoid changing jobs for reasons related to health insurance by about 4.5 percentage points (roughly 55%). This finding is consistent with Hamersma & Kim (2009) & Frasier (2019) show reductions in job lock among enlisted soldiers in the U.S. Army. These differences suggest that parents are more sensitive to changes in health insurance eligibility when it comes to employment stability.…”
Section: Discussionsupporting
confidence: 85%
“…Third, the ACA Medicaid expansions may have benefited adults by reducing job lock, the ability to change jobs or reduce hours due to no longer being tied to a specific job or schedule to maintain employer sponsored health insurance coverage (Madrian, 1994;Rashad & Sarpong, 2008). With a few exceptions (e.g., Callison & Sicilian, 2018;Kofoed & Frasier, 2019), research on adults (not parents specifically), however, has largely found that the ACA expansions did not result in significant changes in employment, job switching, or full-time versus part-time work status (Bailey & Chorniy, 2016;Callison & Sicilian, 2018;Gooptu et al, 2016;Leung & Mas, 2018;Moriya et al, 2016). Previous Medicaid expansions for parents have been linked with reductions in job lock (Hamersma & Kim, 2009), though no known research has examined this question among parents in relation to the more recent ACA expansions.…”
Section: Introductionmentioning
confidence: 99%
“…6 In all, the evidence is quite mixed. Although some studies find small (3%–5%) increases in college enrollment (Jung & Shrestha, 2018; Lopoo et al, 2018; Yaskewich, 2015), including among army veterans (Kofoed & Frasier, 2019), more recent studies using extensive tax-return data find largely null effects (Heim et al, 2018). Heterogenous effects across various subgroups of young adults exposed to this policy change are also documented.…”
Section: Review Of Evidence and Mechanismsmentioning
confidence: 99%